Labor Force Participation Rate and Economic Growth: Observations for Turkey - Bilal Kargi (Universal Journal of Management and Social Sciences, 2014)
Although some discussions about the relation between population and the economic growth are made for a long time, today there is a general opinion that the population growth has positive relation with the economic growth. This opinion is also supported by the empirical studies. Despite there is a growth directly advancing with the population growth, the advancing of the population in the opposite direction with the rate of the labor force participation is thought to be a paradox. This paradox reveals some concepts, namely, "jobless growth" and " unskilled growth". In this study, an explanation is sought about the remaining or less increasing of the rate of the labor force participation although a linear relation between the GDP and the population and the labor. The official statements refer that this paradox is related with the lack of female participation in the labor force and employment in the agricultural sector to be falling. This study tries to point that this quantity cannot create a quality although the growth is quantitative.
Keywords: O40; J01; 330; Economic Growth; Labor Force Participation Rate; Labor Markets; Turkish Economy